Osseointegration evaluation of UHMWPE and PEEK-based scaffolds with BMP-2 using model of critical-size cranial defect in mice and push-out test. (July 2021) - Senatov, F.; Maksimkin, A.; Chubrik, A.; Kolesnikov, E.; Orlova, P.; Krivozubov, M.; Nikitin, K.; Gromov, A.; Karyagina, A.
Abstract: It the present study the push-out mechanical test was adopted for mouse model of implantation in critical-size cranial defects to evaluate the effectiveness of implant-skull fusion. As implants, disks of porous ultra-high molecular weight polyethylene (UHMWPE) and polyetheretherketone (PEEK) with hydroxylapatite (HA) with and without loading of recombinant bone morphogenetic protein-2 (BMP-2) were used. Implantation results were evaluated using histology and micro-computed tomography (micro-CT). In the case of both UHMWPE/HA and PEEK/HA, BMP-2 loading resulted in a significant increase in the amount of bone tissue in the implantation area, especially at the edges of the defect, and an increase in the value of BV/TV (bone volume/tissue volume) during micro-CT. There was a high correlation of BV/TV values with the maximum load and elastic modulus measured during the puch-out test. The maximum load values showed good convergence within the groups and are comparable to the maximum load values obtained by other authors in the rat model of implantation in critical-size cranial defects. An adapted push-out test can be used to evaluate the quality of osseointegration of the implanted materials. Graphical abstract: Image 1 Highlights: Push-out test was adopted for a mouse model of critical-size cranial defects. High correlation was obtained between push-out tests, micro-CT and histological data. Porous UHMWPE/HA and PEEK/HA implants with rhBMP-2 provide bone tissue ingrowth. Quantitative study of implanted materials degree of integration was performed.